Effectiveness of Ethanol Extract and Ethyl Acetate Fraction of Breadfruit Leaves (Artocarpus altilis) as Antihyperglycemia - Daulay, Agus Husein; Siahaan , Jekson Martiar; Syahrir, Lesmana; Tambunan, Ronald Tunggul Hotmarojahan (Indonesian Journal of Medicine, 2024)
Background: The rising diabetes mellitus (DM) population is a public health concern. Pharmacotherapy for DM can cause side effects and is often inaccessible, necessitating alternative therapies like medicinal plants. Breadfruit leaves (Artocarpus altilis) have antidiabetic effects. This study aimed to examine the antihyperglycemic effect of ethanol extract and ethyl acetate fraction of breadfruit leaves on alloxan-induced diabetic male white rats (Rattus norvegicus). Subjects and Method: This was a randomized controlled trial. Sample was 35 male white Wistar rats (Rattus norvegicus sp.) divided into 7 groups. The study was conducted at the Phytochemical Laboratory and Animal House, Faculty of Medicine, Indonesian Methodist University, from April to May 2023. The dependent variables were body weight, blood glucose levels, and diameter of the islets of Langerhans. The independent variables were variations in the dose of ethanol extract and ethyl acetate fraction of breadfruit leaves. Body weight was measured by scales. Blood glucose was measured using glucometer. Diameter of the islets of Langerhans was measured using computer-based image analysis system. Data were analyzed using Anova and Kruskal-Wallis tests. Results: Weight loss was better in the group given the ethyl acetate fraction at a dose of 200 mg/kgBW compared to the other groups. Administration of ethanol extract at a dose of 200 mg/kgBW showed a better reduction in blood glucose levels compared to the other groups, where P < 0.05 between K4 and K3, K5, and K7 on day 5. Ethanol extract at a dose of 200 mg/kgBW was able to improve the diameter of the islets of Langerhans induced by alloxan. Conclusion: A 200 mg/kg BW dose of ethyl acetate fraction reduces body weight. A 200 mg/kg BW dose of ethanol extract reduces blood glucose and improves pancreatic islet diameter.